Binding of HCN channels to GABAB receptors in dopamine neurons of the VTA limits synaptic inhibition and prevents the development of anxiety - Pérez-Garci, Enrique; Pysanenko, Kateryna; Rizzi, Giorgio; Studer, Florian; Ulrich, Daniel; Fritzius, Thorsten; Früh, Simon; Porcu, Alessandra; Besseyrias, Valérie; Melichar, Adolf; Gassmann, Martin; Barkat, Tania Rinaldi; et al. (Neurobiology of disease, 2025)
During GABAergic synaptic transmission, G protein-coupled GABAB receptors (GBRs) activate K+ channels that prolong the duration of inhibitory postsynaptic potentials (IPSPs). We now show that KCTD16, an auxiliary GBR subunit, anchors hyperpolarization-activated cyclic nucleotide-gated (HCN) channels containing HCN2/HCN3 subunits to GBRs. In dopamine neurons of the VTA (DAVTA neurons), this interaction facilitates activation of HCN channels via hyperpolarization during IPSPs, counteracting the GBR-mediated late phase of these IPSPs. Consequently, disruption of the GBR/HCN complex in KCTD16-/- mice leads to prolonged optogenetic inhibition of DAVTA neuron firing. KCTD16-/- mice exhibit increased anxiety-like behavior in response to stress - a behavior replicated by CRISPR/Cas9-mediated KCTD16 ablation in DAVTA neurons or by intra-VTA infusion of an HCN antagonist in wild-type mice. Our findings support that the retention of HCN channels at GABAergic synapses by GBRs in DAVTA neurons provides a negative feedback mechanism that restricts IPSP duration and mitigates the development of anxiety.
Keywords: inhibiční postsynaptické potenciály; Inhibitory Postsynaptic Potentials; Male; Ventral Tegmental Area; Mice, Knockout; dopaminergní neurony; receptory GABA-B; mužské pohlaví; myši knockoutované; Hyperpolarization-Activated Cyclic Nucleotide-Gated Channels; úzkost; Animals; zvířata; tegmentum mesencephali - area ventralis; myši inbrední C57BL; myši; Dopaminergic Neurons; Mice, Inbred C57BL; Receptors, GABA-B; Mice; Anxiety; hyperpolarizační iontové kanály řízené cyklickými nukleotidy